Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1183/13993003.01752-2019
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of patients with chronic breathlessness towards treatment with opioids

Abstract: Breathlessness is the most common symptom in advanced chronic lung disease or chronic heart failure (CHF) [1]. Opioids are recommended for palliative treatment of breathlessness persisting despite optimal pharmacological and non-pharmacological treatment [2, 3]. However, physicians don't always consider opioids for chronic breathlessness [4,5] and experience barriers when considering opioids, such as resistance of patients [6]. This can limit effective palliative treatment. Qualitative studies in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Effective communication of potential benefits and harms of opioids for breathlessness was important 32 and found to improve patient trust in clinicians and patient approval of clinician recommendation of opioids for breathlessness. 39 Poor communication about the use of opioids and potential harms was found to reduce patient willingness and confidence in using opioids to reduce symptomatic chronic breathlessness. 39 Furthermore, a poor relationship between a clinician and the patient’s family was shown to be a potential barrier when there were cultural differences between the clinician and the patient/family.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Effective communication of potential benefits and harms of opioids for breathlessness was important 32 and found to improve patient trust in clinicians and patient approval of clinician recommendation of opioids for breathlessness. 39 Poor communication about the use of opioids and potential harms was found to reduce patient willingness and confidence in using opioids to reduce symptomatic chronic breathlessness. 39 Furthermore, a poor relationship between a clinician and the patient’s family was shown to be a potential barrier when there were cultural differences between the clinician and the patient/family.…”
Section: Resultsmentioning
confidence: 99%
“…Clinician 37 However, older patients were less willing and less confident about using opioids for breathlessness than younger patients, although reasons for this were not explored. 39 Furthermore, the study which highlighted this age difference only received an MMAT total of 2 and was found to have little justification for survey questions as well as limited inclusion and exclusion criteria. This may impact the weighting of the relevance of patient age on opioid use.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations